Mitochondrial Regulation of the Muscle Microenvironment in Critical Limb Ischemia - Ryan, Terence E.; Schmidt, Cameron A.; Green, Tom D.; Brown, David A.; Neufer, P. Darrell; McClung, Joseph M. (Frontiers in Physiology, 2015)
Critical limb ischemia (CLI) is the most severe clinical presentation of peripheral arterial disease and manifests as chronic limb pain at rest and/or tissue necrosis. Current clinical interventions are largely ineffective and therapeutic angiogenesis based trials have shown little efficacy, highlighting the dire need for new ideas and novel therapeutic approaches. Despite a decade of research related to skeletal muscle as a determinant of morbidity and mortality outcomes in CLI, very little progress has been made towards an effective therapy aimed directly at the muscle myopathies of this disease. Within the muscle cell, mitochondria are well positioned to modulate the ischemic cellular response, as they are the principal sites of cellular energy production and the major regulators of cellular redox charge and cell death. In this mini review, we update the crucial importance of skeletal muscle to CLI pathology and examine the evolving influence of muscle and endothelial cell mitochondria in the complex ischemic microenvironment. Finally, we discuss the novelty of muscle mitochondria as a therapeutic target for ischemic pathology in the context of the complex co-morbidities often associated with CLI.